2023
DOI: 10.3390/jcm12041692
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum BAFF Levels with Cardiovascular Events in ST-Segment Elevation Myocardial Infarction

Abstract: Objectives: The B cell activating factor (BAFF) is a B cell survival factor involved in atherosclerosis and ischemia-reperfusion (IR) injury. This study sought to investigate whether BAFF is a potential predictor of poor outcomes in patients with ST-segment elevation myocardial infarction (STEMI). Methods: We prospectively enrolled 299 patients with STEMI, and serum levels of BAFF were measured. All subjects were followed for three years. The primary endpoint was major adverse cardiovascular events (MACEs), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…40 The level of BAFF and PDGF-AB/BB may be increased in combination of elevated cardiac enzymes in patients with post ST-segment elevation myocardial infarction. 41,42 The association of NT proBNP and uPAR was not found in heart failure patients so far, but partially reflect the cardiovasclur risk in Black South African men. 43 Resistin elevation was associated with the occurrence of HF, more significantly with incident HFrEF than HFpEF.…”
Section: Discussionmentioning
confidence: 98%
“…40 The level of BAFF and PDGF-AB/BB may be increased in combination of elevated cardiac enzymes in patients with post ST-segment elevation myocardial infarction. 41,42 The association of NT proBNP and uPAR was not found in heart failure patients so far, but partially reflect the cardiovasclur risk in Black South African men. 43 Resistin elevation was associated with the occurrence of HF, more significantly with incident HFrEF than HFpEF.…”
Section: Discussionmentioning
confidence: 98%
“…Interesting evidence has indicated a significant relationship between specific endogenous factors and AMI. In particular, in a prospective cohort study of STEMI patients who underwent coronary artery angiography, the authors suggested that higher levels of the B cell activating factor (BAFF), a member of the tumor necrosis factor (TNF) superfamily with a significant role in MI/R and atherosclerosis lesions and progression, could represent, in the acute phase, an independent predictor of the incidence of major adverse cardiovascular events in the post-MI period [5]. On the other hand, Ko żuch et al (2022) [6] indicated, in a prospective study, the correlation between growth differentiation factor 15 (GDF-15), as a member of the transforming growth factor superfamily involved in apoptotic and inflammatory pathway regulation, and disturbances in the microcirculatory reflow in patients with STEMI after PCI.…”
mentioning
confidence: 99%